Penetapan Jumlah Setoran Keuntungan oleh Bank pada Pembiayaan Musyarakah Menurut Fatwa DSN-MUI NO 08/DSN-MUI/IV/2000: Studi Kasus Bank Sumut Capem Syariah Binjai - Fadhilah, Nafa Dwi; Tarigan, Tetty Marlina (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This article discusses determining the amount of profit deposits by banks for musyarakah financing. Financing activities are the provision of facilities for providing capital or funds to meet the needs of parties who lack funds/capital or have a unit deficit. This activity is carried out to achieve a profit where the entrepreneur will get business capital and the bank will get a profit. This article also examines the legal basis through the Al-Quran, hadith and DSN MUI fatwa. This research involves a case study at PT. Bank Sumut Capem Syariah Binjai which will provide information to the Bank to pay more attention to everything in accordance with the MUI DSN Fatwa. The research method used is descriptive qualitative with collection techniques through observation, documentation and interviews. The results of the research show that PT Bank Sumut Capem Syariah Binjai has not fully implemented the Musyarakah financing agreement in accordance with the DSN MUI Fatwa, including still determining the amount of profit deposit at the beginning when executing the contract, which is stated in the DSN MUI Fatwa NO 08 DSN-MUI/IV/2000 You should determine the profit deposit at the time of payment each month.